(untitled) (International Journal of Biology and Chemistry, 2018)
One of the main interests of research in the field of medicinal plants is based on the results of potentially active properties of medicinal plants, one of which is current plant - Artemisia sublessingiana known among the locals in Kazakhstan and other Central Asian countries as having healing properties. Definitely, detailed chemical constituents of this herb have not been explored yet. In this study, we have investigated the main bioactive contents of the whole plant A. sublessingiana in terms of its moisture content (10.00 %), total ash (12.42 %), and extractives (22.88 %), also have analyzed the chemical constituents. Therefore, eleven macro- and microelements were identified in the ash of A. sublessingiana by using the method of multi-element atomic emission spectral analysis, and the main elements were K (47.310 %), Ca (41.910 %), Fe (4.984 %), Zn (0.126 %), and Mg (0.3475 %). Moreover, 8 fatty and 20 amino acids were identified from the further chemical investigation of the medicinal plant. Among of them, linoleic acid and oleic acid were recorded as the main components of fatty acids at C18:2 (69.1 %) В and C18:1 (18.3 %) respectively, while glutamate, aspartate and alanine were the major contents of the amino acids at 640 mg/100 g, В В В В В В В В В В В В В В В В 1120 mg/100 g and 890 mg/100 g respectively.